Search for Ancient Selection Traces in Faverolle Chicken Breed (Gallus gallus domesticus) Based on Runs of Homozygosity Analysis - Anna E. Ryabova; Anastasiia I. Azovtseva; Yuri S. Shcherbakov; Artem P. Dysin; Natalia V. Dementieva (Animals)
Runs of homozygosity (ROHs) are continuous homozygous segments of genomes that can be used to infer the historical development of the population. ROH studies allow us to analyze the genetic structure of a population and identify signs of selection. The present study searched for ROH regions in the Faverolle chicken breed. DNA samples from modern individuals and museum Faverolle specimens were obtained and sent for whole-genome sequencing (WGS) with 30× coverage. The results were aligned to the reference genome and subjected to additional filtering. ROH segments were then analyzed using PLINK 1.9. As a result, 10 regions on GGA1, 2, 3, 4, and 13 were identified. A total of 19 genes associated with fat deposition and lipid metabolism (GBE1, CACNA2D1, STON1, PPP1R21, RPL21L1, ATP6V0E1, CREBRF, NKX2-2, COMMD1), fertility (LHCGR, GTF2A1L, SAMD5), muscle development and body weight (VGLL3, CACNA2D1, FOXN2, ERGIC1, RPL26L1), the shape and relative size of the skeleton (FAT4), and autophagy and apoptosis (BNIP1) were found. Developmental protein genes (PAX1, NKX2-2, NKX2-4, NKX2-5) formed a separate cluster. Probably, selection for the preservation of high flavor characteristics contributed to the consolidation of these ROH regions. The present research enhances our knowledge on the Faverolle breed’s genome and pinpoints their ROH segments that are also specific «selection traces».